Keanekaragaman Perifiton Pada Habitat Keong Oncomelania hupensis-linduensis di Desa Dodolo Sulawesi Tengah - Mahfuz Mahfuz; Miswan Miswan; Ramadhanil Ramadhanil (Biology Department, Mathematics and natural science, Tadulako University, 2013)
The research entitled “The diversity of Periphyton at the snail habitat of Oncomelania hupensis linduensis in Dodolo village, Napu Valley, Central Sulawesi has been carried out from July to September 2011. The research took place at Dodolo, Lore Utara District, Poso Regency Central Sulawesi and samples identified at the Labaoratory of Parasitology P2B2 Donggala and the laboratory of Environmental Biology of Department of Biology, Faculty of Mathematics and Natural Sciences, Tadulako University Palu. The samples of Periphyton were collected following Fahri methods (2010) that using artificial substrate which were installed in four (4) research stations namely: ricefield (station I), cacao plantation (station II), resident of local people (station III) and forest garden (station IV). The environmental factor such pH and temperature were observed by Consfort tipe C 933. The data was analysed using Shanon-Whiener Diversity Index. The result showed that there were 35 species of Periphyton which was classified into 18 order and 24 families that consisted of Diatomae Baccilariophyceae and benthic algae. The highest Shanon –Whiener diversity index was found in station II (2.51) and followed by station I (2.23), station III (2.14) and station IV (1.45) respectively. Key words: Perifiton, Dodolo, Napu, Oncomelania hupensis linduensis, Sulawesi Tengah